Implementasi Media Platform Padlet dalam Pembelajaran PAI sebagai Bentuk Melek Digital di Era 4.0 - Muhyidin, Muhyidin; Salsabila, Unik; Fadillah, Ayu Nur; Rifki, Moh; Natifa, Tia (TSAQOFAH, 2022)
This research was conducted to determine the role and implementation of the padlet application as a discussion platform media in Islamic education learning in the 4.0 era. Padlet as an online discussion medium used during this pandemic is quite effective in PAI. Padlets can be used as presentation media such as videos, document files, and so on. The advantage of padlet media is that it can work on any device, be it mobile phones, laptops and computers. The purpose of learning to use this media padlet is to train students in getting used to digital and using it wisely based on the values of Islamic teachings.